(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Anemia during childhood adversely affects mental, physical, and social development of children. Iron shortage can arise even in the absence of anaemia, and this condition might have an impact on the tissues. Different stages of iron insufficiency might present in different ways. When intake of iron falls short of demand, iron reserves are predominantly depleted. The study aims to describe clinical profile of iron deficiency anemia in children of 6 months to 5 years age along with various factors affecting severity. The clinical profile of iron deficiency anemia was studied, and it was found that 27% of children had mild anemia, 60% had moderate anemia, 13% had severe anemia. In our study we found out factors like gestational age, birth weight, malnutrition, mothers’ diet etc were contributing to severity of anemia. Timely initiation of complementary feed is very essential to achieve adequate absorption of iron.